Pengembangan Bahan Ajar Materi Puisi Bergenre Kearifan Lokal pada Siswa Kelas IV Madrasah Ibtidaiyah - Widayanti, Asih; Irfandi, Irfandi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to find out the needs of students in poetry material and to find out the validity of teaching materials for poetry material modules in the genre of local wisdom. This research is a Research and Development (R&D) that is oriented towards developing module teaching materials referring to the Dick and Carrey development model with stages, namely: needs analysis, design development, expert validation and revision. The population is fourth grade students of MI Datok Sulaiman Putra Palopo for the 2021/2022 school year consisting of 27 students. Data were obtained through observations, interviews and test students' thinking skills. To find out the level of validity of the product developed, a validity test was carried out by material expert validators, linguists. The results of this study show that the development of teaching materials for writing poetry in the genre of local wisdom is a very valid category based on expert assessments and several revisions